Human placental cell line HTR-8/SVneo accumulates cadmium by divalent metal transporters DMT1 and ZIP14. Issue 11 (4th November 2020) - Widhalm, Raimund; Ellinger, Isabella; Granitzer, Sebastian; Forsthuber, Martin; Bajtela, Robert; Gelles, Katharina; Hartig, Pia-Yael; Hengstschläger, Markus; Zeisler, Harald; Salzer, Hans; Gundacker, Claudia
Abstract : Placental cells take up Cd via DMT1 and ZIP14 and retain it in Cd-MT2A complexes. Abstract : Cadmium (Cd) is a global pollutant that accumulates in the placenta and can cause placental dysfunction. Although iron transporters have been suggested to participate in placental Cd uptake, it is still unknown which transporters are actually involved in this process. We specifically aimed to study the role of three iron transporters in the uptake of Cd into the placental cell line HTR-8/SVneo. For this purpose, Divalent Metal Transporter (DMT)1 and ZRT/IRT like protein (ZIP)8 and ZIP14 were downregulated and changes in cellular Cd levels analysed in relation to controls. As clearly shown by the reduction of the Cd content by ∼60% in DMT1- and ZIP14-downregulated cells, the two proteins are essential for Cd accumulation in HTR-8/SVneo cells. Using a validated antibody, we show DMT1 to be localised in situ in trophoblast and stromal cells. We further wanted to investigate how placental cells cope with Cd loading and which metallothionein (MT) isoforms they express. Cd-exposed cells accumulate Cd in a dose-dependent manner and upregulate MT2A accordingly (up to 15-fold induction upon 5 μM CdCl2 treatment for 72 h). 5 μM Cd exposure for 72 h decreased cell number to 60%, an effect that was aggravated by MT2A depletion (cell number reduced to 30%) indicating additive effects. In conclusion, our data suggest that DMT1 and ZIP14 are required for Cd uptake into human placental cells that upregulate MT2A to store and detoxify the metal. Cd storage in the placenta reduces Cd transport to the fetus, which, however, could impair placental functions and fetal development.